Fabrication of open type carbonizer for the preparation of activated carbon from rice husk - Dhami, A Kumari; Rajbhandari Nyachhyon, A (BIBECHANA, 2021)
Activated carbon has been prepared from rice husk using laboratory fabricated open type carbonizer. The raw rice husk powder was named RRH whereas chemically activated rice husk was named CARH. Both samples were characterized by methylene blue number (MBN), iodine number (IN), and surface area. The MBN and IN of RRH were found to be 83 mg/g and 415 mg/g whereas CARH was 99 mg/g and 716 mg/g respectively which indicate the presence of mesoporosity and microporosity of the samples. The surface area of RRH was found to be 206 m2/g while CARH was found to be 531 m2/g. XRD analysis showed that the prepared materials were amorphous with some crystalline state while FTIR spectra showed the presence of different functional groups such as hydroxyl, carbonyl, Si-O-Si bond, and aromatic group on the material. The adsorption properties of prepared samples were studied by using Langmuir and Freundlich isotherm models. Langmuir adsorption isotherm model was found to be best fitted. It showed that prepared materials have a homogenous surface with a monolayer type of adsorption. The maximum monolayer coverage (Qm) for RRH was found to be 55 mg/g and for CARH 143 mg/g. Thus, results revealed that laboratory fabricated low-cost open type carbonizer is suitable for the preparation of activated carbon. BIBECHANA 18 (1) (2021) 10-18